2017
DOI: 10.1080/19338244.2017.1305325
|View full text |Cite
|
Sign up to set email alerts
|

Individual and work-related risk factors for musculoskeletal pain among computer workers in Nigeria

Abstract: We investigated the prevalence of musculoskeletal pain (MSP) and the association of 1-month prevalence with individual and work-related factors among commercial typists in Enugu. Participants responded to a questionnaire about occurrences of MSP and a 75.6% (242/320) response rate was achieved. Prevalence was summarized in frequencies and percentages while associations between MSPs and risk factors were explored using chi-square. MSP was most common in the low back (58.3%), and low back pain limited 51.7% from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
2
0
0
Order By: Relevance
“…Additionally, Table 4 also Table 4 also exhibits that duration of working, posture and poor design are the topmost three MSD risk subfactors, since their rank is top three among all other risk subfactors whereas smoking, task/activity type and obesity are the last three risk subfactors. The outcomes of our research are comparable to the prior investigations (Janwantanakul et al 2012;Moom et al 2015;Kaliniene et al 2016;Abaraogu et al 2018;Sasikumar and Binoosh 2020), who reported that heavy duration of working, posture, poor design, and job strain are the subfactors of risks that causes MSD among the HHD users.…”
Section: Relative Weights Calculation/ Priority Of the Subfactors Of Riskssupporting
confidence: 88%
“…Additionally, Table 4 also Table 4 also exhibits that duration of working, posture and poor design are the topmost three MSD risk subfactors, since their rank is top three among all other risk subfactors whereas smoking, task/activity type and obesity are the last three risk subfactors. The outcomes of our research are comparable to the prior investigations (Janwantanakul et al 2012;Moom et al 2015;Kaliniene et al 2016;Abaraogu et al 2018;Sasikumar and Binoosh 2020), who reported that heavy duration of working, posture, poor design, and job strain are the subfactors of risks that causes MSD among the HHD users.…”
Section: Relative Weights Calculation/ Priority Of the Subfactors Of Riskssupporting
confidence: 88%
“…Around two-thirds of online professionals reported the presence of LBP in this study. Our finding is consistent with other studies conducted among computer users who spend long hours in a sitting position [ 17 , 18 ]. Our study results also indicate that long working hours in a sitting position and BMI (overweight/obese) were significant risk factors for LBP.…”
Section: Discussionsupporting
confidence: 93%